2013
DOI: 10.1097/ogx.0b013e318294aff7
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Urinary Incontinence in US Women

Abstract: Introduction and Hypothesis-The goal of this study was to characterize associations between caffeine consumption and severity of urinary incontinence (UI) in US women. We hypothesized that moderate and high caffeine intake would be associated with UI in US women when controlling for other factors associated with UI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Caffeine is known to cause a mild diuresis (Riesenhuber et al 2006;Lohsiriwat et al 2011) which may result in increased urinary frequency and may also affect detrusor stability (Creighton and Stanton 1990). Higher caffeine intakes have been associated with urinary incontinence (UI) (Gleason et al 2013) and caffeine intake has been associated with OAB.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is known to cause a mild diuresis (Riesenhuber et al 2006;Lohsiriwat et al 2011) which may result in increased urinary frequency and may also affect detrusor stability (Creighton and Stanton 1990). Higher caffeine intakes have been associated with urinary incontinence (UI) (Gleason et al 2013) and caffeine intake has been associated with OAB.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few clinical studies have been conducted to investigate the effects of caffeine on overactive bladder symptoms (OAB) and urinary incontinence. It has been reported that coffee increases detrusor overactivity and promotes urge urinary incontinence (UUI) . On the contrary, others reported that caffeine increases the cyclic adenosine monophosphate concentration in the lower urinary tract in rats, which are presenting early stages of diabetes and recovering the micturition reflex by improving the detrusor contractility .…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study demonstrated that high cafeine intake (≥400 mg/day) might cause detrusor overactivity which is related to UUI based on urodynamic evaluation [6]. A recent cross-sectional study, US National Health and Nutrition Examination Survey, further revealed that moderate cafeine intake (≥204 mg/ day) was associated with UI in female population [7]. Based on these inding, some studies were designed to identify the eicacy of cafeine reduction on improvement of UI symptoms.…”
Section: Dietary Modiicationsmentioning
confidence: 99%